Addressing systemic risk in Europe during Covid-19: The role of regulation and the policy mix - Vitor Dotta (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
This work examines the impacts which the Covid-19 pandemic brought to the stability of the European financial sector. Lockdowns, businesses unable to operate and uncertainty about how the pandemic would evolve fueled a sharp recession. From the lessons learned in the global financial crises and the Eurozone debt crises, there's an increasing role of macroprudential policies, especially the regiments of the Basel III framework and the monetary policy toolkit. Alongside macroprudential regulation, the European Central Bank provided substantial monetary policy easing, for instance the release of capital buffers and other capital requirements, expanding the TLTRO III and Pandemic Emergency Program which facilitated monetary policy transmission. Authorities also deployed strong fiscal policies which encompassed from tax holidays to direct transfers to households and firms. The combination of fiscal, monetary, and regulatory policy was unprecedented and helped the economy during the shutdown moments. As a result, indicators of systemic risks in the banking sector during the pandemic remained relatively stable.
Keywords: G21; G28; G38; E58; E62; E63; 330; Systemic Risk; Covid-19 pandemic; banks; banking sector; Europe; Policy Mix; Monetary and Fiscal policy